Long term marginal prices - Solving the revenue reconciliation problem of transmission providers - A. S. D. Braga (2005)
This paper describes a model to perform transmission expansion planning studies together with the computation of Long Term Marginal Prices along the planning horizon. The model includes four criteria and adopts a Simulated Annealing based algorithm to solve the problem. The algorithm also provides Long Term Marginal Prices reflecting both investment and operation costs, thus being able to conveniently address the Revenue Reconciliation Problem that would arise if short-term approaches were used. The paper includes a case study based on the 400/220/150 kV Portuguese transmission system to illustrate the application of the proposed algorithm and highlight its potential.